AGENT-BASED CONTROL ARCHITECTURE TO IMPROVE THE PERFORMANCE OF RFID - Lee, Hae Kyung; Ko, Chang Seong; Kim, Taioun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
To remain competitive in business and to be quick responsive in the warehouse and supply chain, the use of RFID (radio frequency identification) has been increasing in many industry areas. RFID can identify multiple objects simultaneously as well as identifying individual objects respectively. Some limitations of RFID still remain in the low recognition rate and the sensitive response according to the material type and its environment. Much efforts have been tried to enhance the recognition rate and to be more robust. Researches on tag design change, antenna angle, search angle and signal intensity etc correspond to the efforts. The purpose of this paper is to propose an agent-based control system utilizing database, knowledge base and ontology in order to improve the performance of RFID. First, ontology is constructed for the environmental factors to be used as a knowledge base. Second, agent-based RFID manager middleware is created to increase the recognition rate in changing situations. Finally, a thorough experiment is performed to verify the method and contributions using the prototype